Human fibroblasts release reactive oxygen species in response to interleukin-1 or tumour necrosis factor-alpha. - Meier, B (1989)
Human fibroblasts in primary culture released reactive oxygen species upon stimulation with cytokines such as interleukin-1 alpha (IL-1) or tumour necrosis factor-alpha (TNF). The primary radical produced was O2.- as determined by e.s.r. spin trapping and cytochrome c reduction. In contrast to the oxidative burst in granulocytes and monocytes, radical formation took place continuously for at least 4 h. Low-level chemiluminescence was increased by stimulation with IL-1 and TNF. Spectral characteristics and tests with azide led to the conclusion that the photoemissive species were excited carbonyls and not singlet oxygen. Further, there was a liberation of ethane from the cells. Radical production and light emission were not altered by either xanthine or allopurinol, nor by azide, cyanide or rotenone. O2.- production increased in the presence of NADH or NADPH, making an NAD(P)H oxidase a likely source.